Nitrogen Uptake, Not Transfer of Carbon and Nitrogen by CMN, Explains the Effect of AMF on the Competitive Interactions Between Flaveria bidentis and Native Species - Chen, Xue; Li, Qiao; Wang, Liting; Meng, Yanliang; Jiao, Shaona; Yin, Jilin; Xu, Haiyun; Zhang, Fengjuan (Frontiers in Ecology and Evolution, 2021)
Rhizophagus intraradices, one of the common arbuscular mycorrhizal fungi (AMF) grown in the roots of Flaveria bidentis, facilitates the invasion of this exotic plant species into China. However, it is still unknown whether nutrient transfer through the common mycorrhizal networks (CMN) between this exotic species and the native species enhances the competitive growth of F. bidentis over the native species. To elucidate this question and the related mechanism, an isotopic labeling technique was used to test the transfer of carbon (C) and nitrogen (N) by CMN. Native species like Setaria viridis and Eclipta prostrata were selected to compete with F. bidentis in a polyvinyl chloride (PVC) box. Two competitive groups (F. bidentis-S. viridis and F. bidentis- E. prostrata), three treatments (monoculture of F. bidentis, the mixture of F. bidentis and the native plant, and the monoculture of the native plant), and two levels of AMF (presence or absence) were assigned. Results showed that the corrected index of relative competition intensity (CRCI) of F. bidentis in the presence of AMF < 0 suggests that the competition facilitated the growth of F. bidentis with either S. viridis or E. prostrata. The reason was that the inoculation of R. intra radices significantly increased the C and N contents of F. bidentis in the mixtures. However, the effects of R. intra radices on the two native species were different: negative effect on the growth of S. viridis and positive effect on the growth of E. prostrata. The change of N content in S. viridis or E. prostrata was consistent with the variation of the biomass, suggesting that the N uptake explains the effects of R. intraradices on the competitive interactions between F. bidentis and the two native species. Moreover, the transfer of C and N via AMF hyphal links did occur between F. bidentis and the native species. However, the transfer of C and N by the CMN was not positively related to the competitive growth of F. bidentis.